Mobile moralities: Ethical consumption in the digital realm. (November 2018) - Humphery, Kim; Jordan, Tim
Ethical consumption, as a realm of production and exchange, a framework for purchasing decisions and as political activism, is now well established in a range of nations. As a politics, it points to an interconnected but divergent set of concerns centred on issues of environmental sustainability, local and global economic and social justice, and community and individual wellbeing. While the subject of sustained critique, not least because of its apparent privileging of the 'consumer' as the locus of change, ethical consumption has garnered increasing attention. This is most recently evident in the development and widening use of 'ethical consumption apps' for mobile devices. These apps allow the user to both access ethical information on products and, potentially, to connect with a broader politics of consumption. However, in entering the digital realm, ethical consumption also becomes embroiled in the complexities of digital technocultures and their ability to allow users of apps to be connected to each other, potentially building communities of interest and/or activism. This article explores this emerging intersection of the ethical and the digital. It examines whether such digital affordances affect the way ethical consumption itself may be conceived and pursued. Does the ethical consumption app work to collectivise or individualise, help to focus or fragment, speak of timidity, or potential in relation to an oppositional politics of consumption? In confronting these issues, this article suggests that contemporary ethical consumption apps – while full of political potential – remain problematic in that the turn to the digital has tended, so far, to accentuate the already individualising tendencies within a politics of ethical consumption. This speaks also, however, to a similar problematic in the politics of digital technocultures; the use of the digital does not automatically enable – merely through greater connectivity and information availability – forms of radical politics.